Enhancement of 316 L stainless steel mechanical properties through TiC particle introduction via metal powder injection molding - Gu Da; Wu Dun; Chen Zexu; Cao Zheng; Cheng Junfeng; Wang Dong; Lu Xiangyu; Liu Chunlin (Materials Research Express)
Metal powder injection molding (MIM) has been a popular technique in production of alloy materials. Through this technique, near-net-shape alloy products can be molded with one-step production. Stainless steel 316 L (SS 316 L) is an important material in aerospace and marine industry for its excellent material strength and resistance to corrosion. As the industry grows with upgraded techniques, the standard for next generation material strength has improved tremendously. Here we present a practical method strengthening SS 316 L via MIM technique, which might provide a pathway for exploration of high strength materials. TiC was introduced into SS 316 matrix with polyoxymethylene (POM) binder. The metallography indicates that the introduction of TiC facilitates the refinement of the 316 L grain. As the TiC content increases from 0 wt% to 3 wt%, the material properties improve significantly, including a rise in hardness from 151 HV to 301 HV, tensile strength from 689 MPa to 792 MPa, and yield strength from 221 MPa to 339 MPa. Additionally, there is a noticeable reduction in the coefficient of friction and the wear cross-section.